A new species of Pegasus (Syngnathiformes: Pegasidae) from the South China Sea - Zhang, Rongrong; Wang, Xin; Wan, Shiming; Ma, Shaobo; Lin, Qiang (Zootaxa, 2020)
A new fish species from the South China Sea, Pegasus nanhaiensis sp. nov., is described herein. The new species is readily distinguished from all other species of the genus Pegasus with the following characteristics: A rounded hump-like tubercle on each of dorsal plates I, II, and III. Noticeable hexagonal patterns on the dorsal carapace with a clear boundary, and two paired caudolateral plates overlapping the junctions between tail rings II and III, and between tail rings IV and V. The integrated evidence from both morphological and genetic studies indicates that P. nanhaiensis represents an independent lineage within the genus Pegasus.